Operasionalisasi Pemikiran Ijtihad Iqbal dalam Bingkai Proposisi Esensialnya Mutahhari - Chaidaroh, Umi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2007)
Islam and social change are two different sides of two different coins. Theyseem forever separable. But Muslims soon realize that they live within particular socialcontext. This certainly has compelled them to consider how they should deal with Islamvis-Ã -vis the changing reality of human life which is both fast in its quality and massive inits quantity. This paper tries to explore this issue by referring to the thought of MuhammadIqbal and MurtadÃ¢ Mutahhari.